"When" Students Miss School: The Role of Timing of Absenteeism on Students' Test Performance. (April 2017) - Gottfried, Michael A.; Kirksey, J. Jacob
Policy and practice have charged forward with emphasizing the necessity to reduce school absenteeism in the fall (i.e., Attendance Awareness Month). However, no empirical basis served to bolster these efforts. This study examined whether fall versus spring absenteeism was linked to spring state exam scores for a sample of elementary students over 3 years. Using district data, the findings suggested spring absences were associated with lower testing performance, with the most critical period being the 30-day window leading up to the test. This study illustrates that most is at stake for student test performance by missing school in the days and months leading up to the test date and that different support systems are needed to address subgroups of students.